+0  
 
0
66
1
avatar

Solve 3a + 4b = 5a - 6b + 24 - 3a for a in terms of b.

 May 16, 2023
 #1
avatar
0

This is what you have to do:

First what you do is Simplify the equation: 3a + 4b + -5a + 6b = 0

Then just follow the steps below:

Reorder the terms: 3a + -5a + 4b + 6b = 0

Combine like terms: 3a + -5a = -2a -2a + 4b + 6b = 0

Combine like terms: 4b + 6b = 10b -2a + 10b = 0

Solving -2a + 10b = 0

Solving for variable 'a':

Move all terms containing a to the left, all other terms to the right.

Add '-10b' to each side of the equation. -2a + 10b + -10b = 0 + -10b

Combine like terms: 10b + -10b = 0 -2a + 0 = 0 + -10b -2a = 0 + -10b

Remove the zero: -2a = -10b

Divide each side by '-2'. a = 5b

Simplifying a = 5b

 May 16, 2023

2 Online Users

avatar